The conception of Shakarim «Doctrine of conscience» (Eurasian Journal of Philology Science and Education, 2019)
In this article the great Kazakh thinker, philosopher, poet Shakarim Kudaiberdiuly’s conception(1858-1931) «Doctrine of conscience» is considered. Conscience is formed in humanistic of maturehuman qualities. By Shakarim, the doctrine of conscience is through the system step-by-step process ofachievement of all properties in the manner set.The author based on the methodology of historical relativity and the theory of knowledge, analyzing by the start sources and bases of conception of Shakarim «doctrine of conscience» and discloses itsoriginal value. It is paid attention to only comparing of studying the level of inner spiritual power of thisconcept in the world of fundamental spiritual and philosophical doctrines.